SEJARAH DAN PERAN MUHAMMADIYAH DALAM PENGEMBANGAN PENDIDIKAN ISLAM DI INDONESIA: TINJAUAN LITERATURE REVIEW - andi riska (Aqidah-ta: Jurnal Ilmu Aqidah, 2023)
This study aims to provide a literature review regarding the historical description of Islamic education in Indonesia prior to the establishment of Muhammadiyah and the role of Muhammadiyah in developing Islamic education in Indonesia. This research uses literature sources such as books, journals, articles, and other publications that are relevant to this topic. The results of this literature review show that prior to the presence of Muhammadiyah, Islamic education in Indonesia tended to be limited to Islamic boarding schools or traditional educational institutions. Muhammadiyah emerged as an Islamic reform movement that carries religious principles that are more moderate and open to science. This movement advocates for modern Islamic education, with an emphasis on general education that includes both religious and general knowledge. Muhammadiyah established various educational institutions ranging from elementary to tertiary levels, including Muhammadiyah schools and Muhammadiyah University. They are also involved in curriculum development that combines Islamic values with modern science. Keywords: Muhammadiyah, Islamic Education, Development, History